2011
DOI: 10.1590/s1516-44462011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Affective state dependence and relative trait stability of perfectionism in sleep disturbances

Abstract: Despite significant changes in perfectionism mean scores over the follow-up, the correlation analyses demonstrated that participants remained quite stable in regard to their relative levels of perfectionism. As concurrent difficulties initiating sleep also predicted concurrent socially-prescribed perfectionism, this seems to be one dimension of perfectionism with trait-state characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…or adjustment and mental health problems [53], interventions targeting perfectionism are rare and often produce only small effects [54]. Given the relatively high stability of perfectionism across age [55], it is possible that perfectionism is difficult to modify with a brief web-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…or adjustment and mental health problems [53], interventions targeting perfectionism are rare and often produce only small effects [54]. Given the relatively high stability of perfectionism across age [55], it is possible that perfectionism is difficult to modify with a brief web-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown relationships between personality traits/disorders and insomnia particularly those of Clusters C and B. Obsessive compulsive personality disorder and the OCPD trait of perfectionism have been associated with difficulties in falling asleep and other sleep disturbance 5053 in student and general adult samples. Persons with borderline personality disorder have been found to have a poorer overall quality of sleep, and traits have been linked to sleep duration, sleep latency, subjective sleep quality, and also to daytime dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Cox and Enns' (2003) study of patients with current and remitted depression revealed relative stability across the three HFMPS trait dimensions. Further evidence of temporal stability emerged from a recent longitudinal study of perfectionism and sleep with university students in Portugal (see Maia, Soares, & Pereira, 2011).…”
Section: Testàretestmentioning
confidence: 98%